Therapeutic Prospects of Metabolically Active Brown Adipose Tissue in Humans - Betz, Matthias J.; Enerbäck, Sven (Frontiers in Endocrinology, 2011)
The worldwide obesity epidemic constitutes a severe threat to human health and wellbeing and poses a major challenge to healthcare systems. Current therapeutic approaches, relying mainly on reduced energy intake and/or increased exercise energy expenditure, are generally of limited effectiveness. Previously believed to be present only in children, the existence of metabolically active brown adipose tissue (BAT) was recently demonstrated also in healthy human adults. The physiological role of BAT is to dissipate chemical energy, mainly from fatty acids, as heat to maintain body temperature in cold environments. Recent studies indicate that the activity of BAT is negatively correlated with overweight and obesity, findings that raise the exciting possibility of new and effective weight reduction therapies based on increased BAT energy expenditure, a process likely to be amenable to pharmacological intervention.